Prevalence of low back pain and associated factors among taxi drivers in Johor Bahru - Rathakrishnan, Tamil Selvan (2013)
Low back pain is one of the common musculoskeletal disorders affecting taxi drivers in the transportation sector. The problem is frequently associated with prolonged sitting while driving, whole body vibration and manual handling of goods to be delivered. There are approximately 73,893 licences issued for taxi drivers in Malaysia and 10.5% of them are based in the Johor Bahru, most probably due to located in town and near to Singapore. The main objective of this study was to determine the prevalence of low back pain and associated factors among taxi drivers in Johor Bahru for the year 2012. The sample size required for this study was 228 respondents but only 224 respondents were managed to be approached for administration of assisted questionnaire. The response rate of this study was 98.2%. Results showed that the prevalence of low back pain in the past twelve months was 49.1%. Majority of the respondents were Malay (84.4%), and nonsmokers (90.2%). The prevalence of low back pain was higher among those who drove Wira taxis (55.5%), Indian and other ethnicities (56.0%). There was a significant association between low back pain and marital status. Abnormal Body Mass Index (BMI) status was significantly related to low back pain as well, supporting the postulated hypotheses. The study also revealed significant association between low back pain and manual handling, which includes lifting, bending and twisting the lower back. There was a higher prevalence of low back pain among taxi drivers who are not satisfied with their work (66.7%) and among those who lack support at work (53.8%). It was also found that the taxi drivers are highly aware of the low back pain problem and in need for early prevention and treatment. Therefore, necessary interventions need to be implemented to reduce the prevalence of low back pain among taxi drivers to retain them in the job and enhance productivity